Analysis of the Stability of Retaining Walls Using FEM and LEM on the Dumai Duri Kandis Road - Mahardika, Tiara (Jurnal Pendidikan Teknik Bangunan, 2025)
This research aims to analyze and compare the stability of retaining walls using two analytical approaches, namely the Finite Element Method (FEM) and the Limit Equilibrium Method (LEM), on the landslide-prone section of the Dumai Duri Kandis Road. The research was conducted using an exploratory method through field observations, collection of primary and secondary data, and numerical simulations. The research population consists of geotechnical structures in landslide areas, with samples taken from drilling points up to 24 meters deep as the location for soil analysis. The research instruments include a drilling machine, SPT (Standard Penetration Test), and Plaxis 2D and Slide 2 software for FEM and LEM simulations. Primary data were obtained from field soil stratification tests, while secondary data included earthquake maps, plan drawings, and bored pile specifications. Based on soil classification, the location falls within soft soil with an earthquake acceleration of 0.1088g. The analysis results show that the application of bored piles significantly increases the safety factor (SF) value. In conditions without bored piles, the average SF ranges from 1.02 to 1.27, whereas with bored piles, it increases to more than 2.1, depending on the water table conditions and loading. In conclusion, the FEM and LEM methods show that the use of bored piles can increase slope stability by more than 135% compared to without reinforcement. These findings recommend the use of bored piles as an effective reinforcement strategy for road sections with a high potential for landslides.